Synthesis of pyrrolidin-5-one-2-carboxamides through cyclization of N-substituted-2-alleneamides - Shahriari, Azadeh; Amiri, Kamran; Nikbakht, Ali; Rominger, Frank; Bijanzadeh, Hamid Reza; Balalaie, Saeed (The journal of organic chemistry, 2022)
The synthesis of pyrrolidin-5-one-2-carboxamides 6a-p has been developed via a one-pot Ugi reaction of allenic acids, primary amines, isocyanides, and aldehydes followed by regioselective cyclization of the resultant N-substituted-2-allenamides with KOt-Bu at room temperature. The cyclization reaction was carried out through a 5-exo-dig approach, which resulted in good yields and high atom-economy under transition-metal-free and mild reaction conditions.